2014
DOI: 10.1371/journal.pone.0097750
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Long-Term Hyperbaric Oxygen Treatment (HBOT) Administered after Experimental Traumatic Brain Injury in Rats Induces Significant Remyelination and a Recovery of Sensorimotor Function

Abstract: Cells in the central nervous system rely almost exclusively on aerobic metabolism. Oxygen deprivation, such as injury-associated ischemia, results in detrimental apoptotic and necrotic cell loss. There is evidence that repetitive hyperbaric oxygen therapy (HBOT) improves outcomes in traumatic brain-injured patients. However, there are no experimental studies investigating the mechanism of repetitive long-term HBOT treatment-associated protective effects. We have therefore analysed the effect of long-term repet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…We found transient changes in the expression levels of these markers suggesting the potential role of the oxygen in modulating neural and inflammatory signaling cascades, which may lead to the sustained functional changes we observed. Animal models have outlined multiple possibilities for the role of HBOT on antiapoptotic and anti-inflammatory signaling pathways including Nogo-A, bcl-2 for plasticity and TNF, IL-1, IL-6, and COX-2 for inflammation [15,17,30,[61][62][63][64][65][66][67][68][69][70][71][72][73]. However, with blood based markers that are found throughout the body we are unable to make definitive statements about mechanism at this time.…”
Section: Discussionmentioning
confidence: 99%
“…We found transient changes in the expression levels of these markers suggesting the potential role of the oxygen in modulating neural and inflammatory signaling cascades, which may lead to the sustained functional changes we observed. Animal models have outlined multiple possibilities for the role of HBOT on antiapoptotic and anti-inflammatory signaling pathways including Nogo-A, bcl-2 for plasticity and TNF, IL-1, IL-6, and COX-2 for inflammation [15,17,30,[61][62][63][64][65][66][67][68][69][70][71][72][73]. However, with blood based markers that are found throughout the body we are unable to make definitive statements about mechanism at this time.…”
Section: Discussionmentioning
confidence: 99%
“…within 1 week of injury, may be more conducive to improving the prognosis of patients with blast-induced TBI [ 10 ]; (2) dynamic contrast-enhanced magnetic resonance imaging, diffusion-weighted imaging, and venous clinical severity scores in experimental TBI have suggested that HBOT could improve the impaired BBB and cytotoxic edema following TBI and promote the recovery of neurons [ 11 ]; (3) early and timely HBOT intervention can have a more robust effect than delayed intervention, as hypoxia-inducible factor 1-alpha is inhibited and the percentage of apoptotic cells in brain tissue declines dramatically [ 12 ]; (4) trauma-associated neurological impairment regressed significantly following 3 weeks of repeated HBOT, a process that is mediated by pronounced remyelination in the ipsilateral injured cortex, as substantiated by the associated recovery of sensorimotor function. Furthermore, this assumption is confirmed by a pronounced increase in myelin basic protein isoforms [ 13 ]; (5) a single intervention with HBO has a time limitation of 12 h post-TBI, while the superimposition of multiple HBO treatments can extend the post-TBI delivery time window [ 14 ]; (6) in the acute stage, HBOT may improve the outcome of TBI in rats by inhibiting activated inflammation and gliosis, while both angiogenesis and neurogenesis are stimulated [ 15 ]; (7) in mice, interleukin-10 plays an important role in the neuroprotective effect of HBOT against TBI, which is associated with resisting neuroinflammation [ 16 ]. Above all, the neuroprotective effect of HBOT against TBI has been observed by comparing superficial phenomena and from the levels of some specific proteins, signaling pathways and targeting genes.…”
Section: Animal Studiesmentioning
confidence: 92%
“…And it is possible that HBOT has a positive effect in a subgroup of patients with moderate injury but not in those with extensive cerebral injury. Repetitive long-term HBO treatment following TBI would have more pronounced effects and might modulate different cerebral functions than short-term treatment during the acute phase of TBI only (Kraitsy et al, 2014).…”
Section: Issues Affect the Efficiency Of Hbot In Tbimentioning
confidence: 99%